Recombinant Escherichia coli producing an immobilised functional protein at the surface of bio-polyester beads : a novel application for a bio-bead : a thesis presented in partial fulfillment of the requirements of the degree of Master of Science in Microbiology at Massey University, Palmerston North, New Zealand - Atwood, Jane Adair (Massey University, 2008)
Polyhydroxyalkanoates (PHAs) are polyesters, produced by many bacteria and some archaea. The most commonly characterised is polyhydroxybutyrate (PHB). Produced when nutrients are growth limiting and carbon available in excess, PHA serves as a carbon-energy storage material and forms generally spherical insoluble inclusions between 50-500nm in diameter in the cytoplasm. The key enzyme for PHA synthesis is the PHA synthase and this enzyme catalyses the polymerisation of (R)-3-hydroxy fatty acids into PHA. PHA synthase remains covalently attached to the growing polyester chain and is displayed on the surface of the PHA granule. Other proteins associated with PHA granules include depolymerases for mobilisation or degradation of granules, regulatory proteins and phasins, proteins that aid in PHA granule stability. PHA bio-beads displaying an IgG binding protein were produced and used to purify IgG from serum demonstrating that the PHA synthase can be engineered to display functional synthase fusion proteins at the PHA granule surface. Correctly folded eukaryotic proteins were also produced and displayed at the PHA granule surface as phasin fusion proteins. Multiple-functionality was also achievable by co-expression of various hybrid genes suggesting that this biotechnological bead production strategy might represent a versatile platform technology. The production of functional eukaryotic proteins at the PHA bead surface represents a novel in vivo matrix-assisted protein folding system. Protein engineering of PHA granule surface proteins provides a novel molecular tool for the display of antigens for FACS based analysis and offers promising possibilities in the development of future biotechnological production processes. Overall, the results obtained in this study strongly enhance the applied potential of these polyester beads in biotechnology and medicine.
Keywords: Escherichia coli; Biopolyester beads; Bio-beads; Polyhydroxyalkanoates; Polyhydroxybutyrate; Protein engineering; Fields of Research::270000 Biological Sciences::270300 Microbiology::270306 Microbial genetics